PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN NGAWI DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Rahayu Triastity, Eko Purnomo & (Universitas Slamet Riyadi, 2017)
This study aims to analyze the influence of leadership style andmotivation to employee performance with the discipline of work as anintervening variable. This study uses survey method, the type of data usedquantitative and qualitative data, the data source used primary data andsecondary data. The population in this study were all employees of theRegional Secretariat Ngawi which amounted to 165 employees. The numberof samples in this study as many as 82 employees, with a samplingtechnique using proportional cluster random sampling. Data collectionmethods are used: a questionnaire. Data analysis technique used to test thevalidity, reliability test, classic assumption test, and path analysis.The resultsof data analysis we concluded that: (1) significantly influence the leadershipstyle of discipline of employees working at the Regional SecretariatEmployees Ngawi. (2) Motivation significant effect on employee workdiscipline at the Regional Secretariat Ngawi. (3) The leadership style have asignificant effect on the performance of employees in the RegionalSecretariat Ngawi (4) Motivation significant effect on the performance ofemployees in the Regional Secretariat Ngawi. (5) working Disciplinesignificant effect on the performance of employees in the RegionalSecretariat Ngawi. (6) Discipline working mediate the effect of leadershipstyle on employee performance in the Regional Secretariat Ngawi. (7)working Discipline mediate the effect of motivation on employee performancein the Regional Secretariat Ngawi.Keywords: leadership style, motivation, work discipline, employeeperformance